تاثير التدريب التكراري بأستخدام مركب فوسفات الكرياتين في تطوير بعض المهارات بكرة اليد - كنعان, محمد ابراهيم; محمود, نوفل محمد; ابراهيم, أحمد سليمان (Sulaimani Journal for Humanities, 2018)
The importance of research through the interest of the training process using a food supplement by developing a training program using one of the important training methods in a repetitive training method. The aim of the research is to prepare the training program using the creatine phosphate compound in developing some skills in handball And the hypothesis of research There are significant differences between the tests of tribal and remote and for the benefit of the post-test and the two groups of research. The research sample included the players of Sulaimaniyah Sports Club handball where the research community (20) players were divided into two experimental groups and the number of (8) players for each group after the exclusion of the goalkeepers and the number (4) as the first experimental group used creatine in the style of ascending With the application of the training program, but the second experimental group used creatine in the style of the downlight with the application of the training program has been homogenization of the two samples so as not to affect the conduct of test results. The training program included 27 training units with three training units. The program took 9 weeks. The training time was 90 minutes. The training program was implemented from 10/1/2016 until 10/3/2016. The data was collected, emptied and then processed (T test). The following conclusions were reached: The effectiveness of the repeat training using the creatine phosphate compound led to the development of some skills in the experimental research groups between the pre-test and the test and for the post-test. The repetitive training method has played an active role in the development of some of the basic skills of (accuracy of correction and the strength of twists and defensive moves) of handball players.